Examinando el papel de la educación ambiental en la construcción del buen vivir global: contribuciones de la corriente crítica a la definición de objetivos - Rafael SUÁREZ-LÓPEZ; Marcia EUGENIO; Fernando LARA; David MOLINA-MOTOS (Revista Iberoamericana de Estudios de Desarrollo)
In this paper, it is examined the role that environmental education plays in the development of global good living. Environmental education is introduced, its trajectory and evolution are reviewed in multiple currents, and the predominant one, education for sustainable development, is described, stressing on its implicit conceptions and shortcomings. Then, critical environmental education is presented, which spurns the uniformity of global capitalism and teaches the old and the new roots to our land and to the Earth, and a plural and diverse sense of collective and individual identity. We focus on its proposals in relation to ecologism, criticism, sustainability, interculturality, and participation. Afterwards, we reflect on some specific characteristics that the pedagogical proposal of critical environmental education should have for the construction of global good living. Finally, a good living goal is proposed.